COVID-19 Compliance and Media Consumption: A Longitudinal Study of Finland and the US During the First Year of COVID-19 - Koivula Aki; Räsänen Pekka; Marttila Eetu; Sedgwick Donna; Hawdon James (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
The article examines media consumption and compliance with health-protective measures during the COVID-19 pandemic. Two-wave, longitudinal surveys were conducted in Finland and the United States in April 2020 and October 2020, with a total of 1,380 participants (N = 1,380). The variables analyzed included daily consumption of different media channels (broadcast, print, and social media), health-protective behavior, and COVID-19 self-efficacy. The results indicated that individuals who consumed more than one media channel on a daily basis exhibited increased health-protective behavior and COVID-19 self-efficacy in both countries. One-sided and social media-based media consumption showed a negative association with health-protective behavior and COVID-19 self-efficacy in both countries. Finally, COVID-19 self-efficacy was found to mediate the relationship between media consumption and health-protective behavior in both countries, with a stronger effect observed in the United States.